Vegetating plaques in the groin: A manifestation of metastatic crohn's disease - Chetana Jagatgere Math; Anju George (Wolters Kluwer Medknow Publications, 2018)
Crohn's disease (CD) is a type of inflammatory bowel disease that can affect any part of the gut from mouth to anus. It also may occur at contiguous sites, like, lip, perineal or peristomal regions or may occur at sites separated from the bowel by normal tissue referred to as metastatic CD. The condition is relatively rare and may mimic or coexist with other dermatoses. The presence of noncaseating granuloma on histopathological examination confirms the diagnosis. Here, we report a case of metastatic CD with cutaneous symptoms of long duration and presenting with vegetating plaques in the lower abdomen, groins, and vulva. The gastrointestinal disease was under remission. The diagnosis was confirmed by histopathological examination and patient responded well to topical as well as systemic steroids.